Policy Model Based on Islamic Approach To Create Equality For Human - Makatita, Armin Rusli; Makatita, Gamal Abdul Nasir; Lamba, Jessica Gafur (The Indonesian Islamic Studies and International Relations Association (Insiera), 2024)
Humanitarian crises are a phenomenon that continues to emerge from time to time. Even though the world has entered the modern era, humanitarian crises still hit humanity. A humanitarian crisis is a condition in which the fundamental rights of a human being are not fulfilled. Humanitarian crises significantly affect entire communities or groups of people in an area. Several factors cause humanitarian crises: political unrest, war, environmental causes, health service emergencies, population displacement, hunger and malnutrition, and lack of essential services. This research aims to comprehensively examine appropriate policy models in dealing with humanitarian crises based on Islamic understanding while re-emphasizing the role of religion in resolving the current humanitarian crisis. The type of research in this research is a qualitative literature review, the data source is from various literature. Result shows that humanitarian crises can be overcome by taking multiple approaches, such as creating good governance, prioritizing all aspects of goodness in doing things, and strengthening the philanthropy system, especially Islamic philanthropy, to meet the short-term needs of victims of humanitarian crises.